Jews and words - Oz, Amos, 1939-2018; Oz-Salzberger, Fania (Yale University Press, 2012)
The authors roam the gamut of Jewish history to explain the integral relationship of Jews and words. Father and daughter tell the tales behind Judaism's most enduring names, adages, disputes, texts, and quips. These words, they argue, compose the chain connecting Abraham with the Jews of every subsequent generation. From the unnamed, possibly female author of the Song of Songs through obscure Talmudists to contemporary writers, they suggest that Jewish continuity, even Jewish uniqueness, depends not on central places, monuments, heroic personalities, or rituals but rather on written words and an ongoing debate between the generations.